First report on mycetoma in Turkana County-North-western Kenya. - María Francisca Colom; Consuelo Ferrer; John Lochuke Ekai; David Ferrández; Laura Ramírez; Noelia Gómez-Sánchez; Simion Leting; Carmen Hernández (Public Library of Science (PLoS), 2023)
Mycetoma is one of the six Neglected Tropical Diseases that are prevalent in Turkana County (northwest Kenya). The aim of the study was to estimate the prevalence of mycetoma in the county, as well as to describe the main causative agents involved in the disease using methods affordable locally. Based on the data collected by the team of cooperative medicine Cirugia en Turkana (Surgery in Turkana), a specific study for mycetoma was started during the 16th humanitarian medicine campaign in February 2019. Patients with suspected mycetoma were studied at the Lodwar County Referral Hospital (LCRH). After informing the patient and getting their consent, the lesions were examined and sampled (mainly by biopsy) and clinical data were recorded. Samples were washed in sterile saline solution and cut in fragments. Some of these were inoculated on Sabouraud Dextrose Agar, Malt Extract Agar, and diluted Nutrient Agar plates. One fragment of each sample was used for DNA extraction. The DNA and the rest of the fragments of samples were kept at -20°C. All cultures were incubated at room temperature at the LCRH laboratory. The DNA obtained from clinical samples was submitted to PCR amplification of the ITS-5.8S and the V4-V5 16S rRNA gene region, for the detection and identification of fungi and bacteria respectively. From February 2019 till February 2022, 60 patients were studied. Most of them were men (43, 74,1%) between 13 and 78 y.o. (mean age 37). Half of the patients were herdsmen but, among women 40% (6) were housewives and 26.7% (4) charcoal burners. Lesions were mainly located at the feet (87.9%) and most of the patients (54; 93.1%) reported discharge of grains in the exudate, being 27 (46.6%) yellow or pale colored and 19 (32.8%) of them dark grains. Culture of clinical samples yielded 35 fungal and bacterial putative causative agents. Culture and molecular methods allowed the identification of a total of 21 causative agents of mycetoma (39.6% of cases studied). Most of them (17) corresponded to fungi causing eumycetoma (80.9%) being the most prevalent the genus Madurella (7; 41.2%), with two species involved (M. mycetomatis and M. fahalii), followed by Aspergillus (2; 11.8%). Other minority genera detected were Cladosporium, Fusarium, Acremonium, Penicillium, and Trichophyton (5.9% each of them). Actinobacteria were detected in 19.1% of samples, but only Streptomyces somaliensis was identified as a known agent of mycetoma, the rest being actinobacteria not previously described as causative agents of the disease, such as Cellulosimicrobium cellulans detected in two of the patients. Although Kenya is geographically located in the mycetoma belt, to our knowledge this is the first report on mycetoma in this country from 1973, and the first one for Turkana County.